17β-Estradiol activates Cl− channels via the estrogen receptor α pathway in human thyroid cells. Issue 1 (1st January 2021) - Yu, Meisheng; Wei, Yuan; Zheng, Yanfang; Yang, Lili; Meng, Long; Lin, Jiawei; Xu, Peisheng; Mahdy, Sanaa Ahmed Nagi Abdu; Zhu, Linyan; Peng, Shuang; Chen, Lixin; Wang, Liwei
ABSTRACT: Estradiol regulates thyroid function, and chloride channels are involved in the regulation of thyroid function. However, little is known about the role of chloride channels in the regulation of thyroid functions by estrogen. In this study, the effects of estrogen on chloride channel activities in human thyroid Nthy-ori3-1 cells were therefore investigated using the whole cell patch-clamp technique. The results showed that the extracellular application of 17β-estradiol (E2) activated Cl − currents, which reversed at a potential close to Cl − equilibrium potential and showed remarkable outward rectification and an anion permeability of I − > Br − > Cl − > gluconate. The Cl − currents were inhibited by the chloride channel blockers, NPPB and tamoxifen. Quantitative Real-time PCR results demonstrated that ClC-3 expression was highest in ClC family member in Nthy-ori3-1 cells. The down-regulation of ClC-3 expression by ClC-3 siRNA inhibited E2-induced Cl − current. The Cl − current was blocked by the estrogen receptor antagonist, ICI 182780 (fulvestrant). Estrogen receptor alpha (ERα) and not estrogen receptor beta was the protein expressed in Nthy-ori3-1 cells, and the knockdown of ERα expression with ERα siRNA abolished E2-induced Cl − currents. Estradiol can promote the accumulation of ClC-3 in cell membrane. ERα and ClC-3 proteins were partially co-localized in the cell membrane of Nthy-ori3-1 cells after estrogen exposure. The results suggest that estrogen activates chloride channels via ERα in normal human thyroid cells, and ClC-3 proteins play a pivotal role in the activation of E2-induced Cl − current.